Integrating STEM education and socio-scientific issues: Impacts on student creativity - Hayati, Nafa Navi'a; Setiono, Setiono; Windyariani, Sistiana (JPBIO (Jurnal Pendidikan Biologi), 2025)
Creativity is an essential 21st-century skill that students must develop to solve real-life scientific and environmental problems. This study aims to determine the effect of the STEM-Socio Scientific Issues learning model on students' creativity in the concept of organic waste management. Students' creativity is measured based on four indicators according to Torrance, namely fluency, flexibility, originality, and elaboration. This study uses a quasi-experimental method with a non-equivalent control group design. The research subjects consist of two classes at Muhammadiyah High School in Sukabumi City. Data were collected through creativity tests in the form of pretest and posttest essay questions that had been validated and reliability-tested. The results showed that the STEM-SSI learning model significantly improved students' creativity, particularly in the aspects of fluency (N-Gain 0.4031), flexibility (0.3029), and originality (0.3017), with a moderate category. However, on the elaboration indicator, the control class achieved a slightly higher N-Gain score (0.3574) compared to the experimental class (0.3396), indicating that this aspect has not developed optimally in STEM-SSI learning. Nevertheless, since three out of four creativity indicators showed significant improvement in the experimental class, it can be concluded that STEM-SSI learning can enhance students' creativity, particularly in terms of fluency, flexibility, and originality.